The effect of lipid sources on intake, rumen fermentation parameters and microbial protein synthesis in Nellore steers supplemented with glycerol - Gomez Insuasti, Arturo Samuel [UNESP]; Granja Salcedo, Yury Tatiana [UNESP]; Castagnino, Pablo de Souza [UNESP]; Vieira, Bruno Ramalho [UNESP]; Malheiros, Euclides Braga [UNESP]; Berchielli, Telma T. [UNESP] (Csiro Publishing, 2014)
The effects of glycerol with fat sources as a feed alternative were investigated in the ration for Nellore steers (Bos indicus). Eight cannulated steers at 30 months of age with initial bodyweight of 554 +/- 36.0 kg were used in a double 4 by 4 Latin square design with four consecutive 16-day periods. Treatments were three different diets with lipid sources (soybean, soybean oil and calcium salts of fatty acids) and one diet control without lipid sources. All diets formulated contained 10% crude glycerol and 5% ether extract with a forage : concentrate ratio of 35 : 65; corn silage was used as forage. The ruminal liquid was sampled for 24 h and ruminal fermentations were monitored by measuring pH, concentrations of ammonia nitrogenand volatile fatty acids in rumen fluid. Urine samples were obtained from the total collection for 24 h for estimation of rumen microbial protein supply using urinary purine derivatives. Our results showed that the use of lipid sources combined with glycerol did not induce significant changes in rumen pH, acetate molar proportion, ruminal microbial protein or dry matter intake. Although the acetate molar proportion was kept constant within normal parameters, the propionate molar proportion was increased by the diet containing lipid sources. Moreover, we found that there was a negative effect of lipid sources on crude protein and neutral detergent fibre corrected for ash and protein intake, and one positive effect on ether extract intake. We believe that association between fat and glycerol may affect rumen fermentation parameters through reducing fibre intake and increasing propionate production and ammonia nitrogen.
Keywords: glycerol; intake of dry matter; lipid sources; microbial protein; rumen fermentation